DEVELOPING EFFECTIVE MARKETING ACTIVITIES TO SUPPORT TOURISM ORGANIZATIONS IN OUR COUNTRY (International journal of artificial intelligence, 2025)
To select and develop a development strategy for tourism enterprises and organizations, managers need timely information, including its search, processing, and analysis. These processes are typically costly. This increases the cost of tourism services and, consequently, negatively impacts their competitiveness in the global market. This article describes the development and implementation of mechanisms for the efficient use of these costs.